2011
DOI: 10.1371/journal.pone.0025907
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Salutary Effects of Astringinin on Rodent Hepatic Injury following Trauma-Hemorrhage: Akt-Dependent Hemeoxygenase-1 Signaling Pathways

Abstract: Astringinin can attenuate organ injury following trauma-hemorrhage, the mechanism remains unknown. Protein kinase B/hemeoxygenase-1 (Akt/HO-1) pathway exerts potent anti-inflammatory effects in various tissues. The aim of this study is to elucidate whether Akt/HO-1 plays any role in astringinin-mediated attenuation of hepatic injury following trauma-hemorrhage. For study this, male Sprague-Dawley rats underwent trauma-hemorrhage (mean blood pressure 35–40 mmHg for 90 min) followed by fluid resuscitation. A sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…In this study, hepatic IL-6, TNF-α, and MIP-1α levels were significantly attenuated in the animals treated with tropisetron after trauma-hemorrhage. Tissue MPO activity is an important indicator of neutrophil infiltration, and it has been correlated with CINC-1 and CINC-3 expression after trauma-hemorrhage [12], [18]. Our results showed that trauma-hemorrhage results in a significant increase in hepatic cytokine/chemokine levels and ICAM-1 expression, which are accompanied by elevated hepatic MPO activity.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…In this study, hepatic IL-6, TNF-α, and MIP-1α levels were significantly attenuated in the animals treated with tropisetron after trauma-hemorrhage. Tissue MPO activity is an important indicator of neutrophil infiltration, and it has been correlated with CINC-1 and CINC-3 expression after trauma-hemorrhage [12], [18]. Our results showed that trauma-hemorrhage results in a significant increase in hepatic cytokine/chemokine levels and ICAM-1 expression, which are accompanied by elevated hepatic MPO activity.…”
Section: Discussionsupporting
confidence: 49%
“…IL-6 is an important pro-inflammatory mediator in hepatic damage and is required for chemokine production and adhesion molecule expression. Liver injury or hypoxia causes marked increases in hepatic IL-6 expression [18], [26]. In this study, hepatic IL-6, TNF-α, and MIP-1α levels were significantly attenuated in the animals treated with tropisetron after trauma-hemorrhage.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…It serves as a protective factor by as it has anti-inflammatory, anti-apoptotic and anti-proliferative properties. These beneficial effects are due to the metabolites of HO-1 (CO, biliverdin and free iron) (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of IL-10 has been shown to promote the expression of inflammatory cytokines, reduce insulin signaling and activate gluconeogenic and lipidogenic pathways in an animal model of diet-induced fatty liver disease (19). In addition, the upregulation of HO-1 has been shown to induce a reduction in the levels of cytokines, adhesion molecules, chemokines and neutrophil accumulation, and to ameliorate organ injury in a state of shock (20)(21)(22). As previously demonstrated, the induction of HO-1 reduces hepatic ischemia reperfusion injury (23), hepatic injury after trauma hemorrhage (24) and renal oxidative stress in diabetic SHRs (25).…”
Section: Cdaa Diet --------------------------------------------------mentioning
confidence: 99%